The Problem Of Fear In Psychology - Orisheva Pokiza Ganisherovna (Academia One, 2024)
The article presents fear, analysis of fear by scientists, situations that cause fear, phobias, types of phobias, the impact of phobias on the human nervous system, as well as important recommendations for parents, teachers and psychologists.
Keywords: fear; phobia; sthenic; asthenic